Carrying Capacity Assessment Based on Chlorophyll-a in the Putus Lake, Siak Hulu Sub-District, Kampar District Riau Province - Ella Dabella Manja; Tengku Dahril; Asmika Harnalin Simarmata (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTThe carrying capacity is defined as the ability of aquatic environment to support the life of organisms in that area. A study aimed to assess the aquatic carrying capacity for extensive fishing in the Putus Lake, Pangkalan Baru Village, Kampar District, Riau. The carrying capacity was determined based on primary productivity using chlorophyll-a concentration, which is indicating the existence of phytoplankton in waters.This research was conducted July, 2019. There were 3 stations namely station 1 (inlet area), station 2 (in the middle of lake) and station 3 (tip of lake). In each stations, there were 2 sampling sites, in the surface and in the middle of water column. Sampling was done four times, once week. Water quality parameters measured transparency, temperature, pH, dissolved oxygen, phosphate and nitrate concentration. Results shown that chlorophyll-a concentration: 10.87-13.19 µg/L, transparency: 66.6-74.2cm, temperature: 29-31 oC, pH: 5, dissolved oxygen: 3,72-5,32mg/L, phosphate: 0,03-0,05mg/L and nitrate: 0.02-0.04mg/L. The concentration of chlorophyll-a indicates that the carrying capacity of the Putus Lake for extensive fishing was 1.73 tons/year.Keyword: oxbow lake, extensive fishing, phytoplankton, water quality